Aktivitas Sosial-Ekonomi di tahun 1930 Kajoetangan (Klojen) serta pemukiman Etnies Tionghoa (Petcinan) - Ahmad Anton Rizqika Walikrom; Khoirurrosyidin; Rinikso Kartono (Academy of Education Journal, 2026)
In discussing “place” Schulz (1984), has explained that there are three important and interrelated concepts, namely character, identity, and genius loci. Methodology: used in writing this research is the Historical method, this is based on the study that will be discussed is a historical study and the data needed in writing the research comes from the past. Discussion: “Genius loci” is a concept behind the physical and socio-cultural aspects. This genius loci can only be understood through a deep understanding of the factors that have shaped the environment. Furthermore, Schulz (1984) put forward 8 Characters of the Area and Architecture of Malang City, East Java, that genius loci is the spirit of the place (spirit of place) where the spirit makes the place “alive” and the place has character.